2013
DOI: 10.1063/1.4858716
|View full text |Cite
|
Sign up to set email alerts
|

The concentration and distribution of selected heavy metals (Pb, Cd, Cu and Zn) in soils collected from the rice fields of MADA in Kedah, Malaysia

Abstract: Abstract. The present study was carried out to determine the concentration and distribution status of some heavy metals (Pb, Cd, Cu and Zn) in the paddy field soil fractions of MADA in the state of Kedah, Malaysia. Five replicate samples were randomly collected from five paddy fields in the MADA area of Jitra. The heavy metals in the soil were extracted using sequential extraction method that was presented by Badri and Aston [1], which consisted of four different fractions using different reagents. The first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
1
Order By: Relevance
“…All metal values in the present research identified below permissible limits for all treatments. Findings of Alrawiq et al [32] showed a higher amount of metals than the presented values in this study except for Cd. Many studies performed in Pakistan reported on the high concentration of trace metals in vegetables irrigated with industrial water or sewage sludge.…”
Section: Trace Metal Concentration In Soil Samplescontrasting
confidence: 60%
“…All metal values in the present research identified below permissible limits for all treatments. Findings of Alrawiq et al [32] showed a higher amount of metals than the presented values in this study except for Cd. Many studies performed in Pakistan reported on the high concentration of trace metals in vegetables irrigated with industrial water or sewage sludge.…”
Section: Trace Metal Concentration In Soil Samplescontrasting
confidence: 60%
“…The significant higher level of As concentration can be found in stem of paddy plants located in the KBP sampling sites and paddy leaf located in PPP sites. These parts are highly accumulated with As, indicating high availability of As in the soil in addition to its mobility within the plants [ 24 ]; concentration may be also influenced by various anthropogenic practices such as farming tractors, chemical fertiliser and pesticide usage [ 29 ]. The arsenic distribution from the root to grain of the paddy plant from the three plots (PPP1, PPP2, PPP3) ranged from 0.078 to 0.087 mg/kg for As concentration, in which the concentration of As in PPP sites was highest in leaf and grain of paddy plants.…”
Section: Resultsmentioning
confidence: 99%
“…The elevated level of Cr in the rice grain from the Pasir Puteh area may be a consequence of anthropogenic contamination in the vicinity of the paddy field. Although Cr is considered an essential element, excessive levels in food or plants may cause toxicity to animals and humans [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation